Reducing the wait: TCV can expand the donor pool for heart transplant candidates. (23rd March 2021) - Szugye, Nicholas A.; Moore, Ryan A.; Dani, Alia; Lorts, Angela; Zafar, Farhan; Morales, David L. S.
Abstract: A 16‐year‐old with new‐onset dilated cardiomyopathy underwent VAD placement, later complicated by low flow from outflow graft kinking. To expedite heart transplantation, TCV was calculated and compared with 141 normal patients pinpointing the upper weight threshold. He was transplanted 2 days later within the expanded weight range with no post‐transplant complications.